A new method for nondestructive fault diagnosis of reciprocating compressor by means of strain-based p–V diagram. (1st November 2019) - Li, Xueying; Peng, Xueyuan; Zhang, Zetian; Jia, Xiaohan; Wang, Zhizhong
Graphical abstract: Highlights: A non-destructive fault diagnosis method for reciprocating compressor is proposed. The p-V diagram is reconstructed based on feature points of piston rod load curve. The quantitative indicators of p-V diagram is applied for comparative analysis. The method is validated by successful identification of typical valve faults. Abstract: As an established method to analyse the thermodynamic process inside a cylinder, the pressure–volume (p–V) diagram can identify typical faults within industrial reciprocating compressors, such as leakages through the sealing rings and self-acting valves, and loosening and fluttering of the valves. However, the installation of a pressure sensor within the cylinder for recording the p–V diagram may lead to degraded strength and potential leakage associated with the cylinder and hence, deteriorated integrity of the cylinder. This study proposes a new nondestructive method to record the p–V diagram of the reciprocating compressor by measuring the piston rod strain. An algorithm for reconstructing the p–V diagram was proposed based on the key feature points on the piston rod load curve that reflects the opening and closing events of the compressor valves. The algorithm was validated by comparing the p–V diagrams obtained from direct pressure measurement and strain-based derivation. The reconstructed p–V diagrams were further used for the fault diagnosis of the reciprocating compressors. The results indicate that this method is able to easily monitor the operating conditions and identify whether and where faults such as leakage and fluttering of the valves occur, and it can be utilized as a powerful tool in the nondestructive condition monitoring and fault diagnosis of the reciprocating compressors.